(untitled) (Current Horticulture, 2024)
An experiment was conducted to utilize the fruits of doka stage of date palm varieties for preparation of nutritious dry date (Phoenix dactylifera L.) i.e. chhuhara, at CIAH, Bikaner, during 2016-17. Dry dates were prepared by giving boiling water treatment of doka (hard ripen) fruits for 4-5 minutes and 8-10 minutes of four date palm cultivars fruits which were drying up to 20-30 per cent moisture content. The dry dates prepared by giving treatment in boiling water for 8-10 minutes and then drying was found suitable in term of recovery percentage and organoleptic score basis for taste, appearance and acceptability as well as nutritive point of view.